PENINGKATAN KAPASITAS UMKM FLORIST MELALUI PELATIHAN APLIKASI DIGITAL UNTUK PEMESANAN BUKET BUNGA DAN MANAJEMEN PELANGGAN - Agustian Syahputra; Muhammad Thaherudin; Rika; Sifa Paujia; Mochamad Albar Mulya (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
The florist business (flower arrangement services) is an important segment of the creative and service-based micro-enterprises in Indonesia. However, most florists operate using traditional manual systems for order booking, customer management, and service coordination. This Community Service Program (PKM) aimed to enhance the operational capacity of Toko Bunga Fajar Florist through training and implementation of a digital application for flower bouquet orders and customer relationship management. The program consisted of: (1) needs assessment and capacity evaluation; (2) digital application development tailored to florist business requirements; (3) comprehensive training program for business owners and staff; and (4) post-implementation mentoring and performance monitoring. The application features include online flower catalogue, real-time order booking, customer database management, pricing automation, delivery tracking, and simple business analytics. Participants included 1 owner and 4 staff members (5 total). Results after 6 weeks of implementation showed: order volume increased 38%, average order value increased 32%, customer database grew from 40 to 156 customers, customer repeat rate improved from 22% to 51%, staff productivity increased 28%, and operational errors reduced by 72%. Training participant satisfaction reached 90% with strong competency achievement. Qualitative feedback indicated significant improvement in customer service quality and business confidence